(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The vast and dynamic maritime domain demands constant observance and accurate information for successful naval operations. However, traditional methods struggle to keep pace with the ever-increasing complexity and data overflow. The paper explores how Artificial Intelligence (AI) presents a transformative opportunity, significantly impacting naval operation by enhancing Situational awareness (SA) and Threat monitoring (TM). It is analyzed the impact of AI across three key areas: enhanced data processing and analysis, improved anomaly detection and predictive capabilities, and real-time decision support. By analyzing key principles, tactics, and procedures for AI implementation, it is explored the process how these capabilities can convert into practical applications and benefits. Examples like AI-powered maritime surveillance and predictive systems for naval assets demonstrate solid benefits of this technological progress. Additionally, in the paper are envisioned future operational scenarios where AI-driven autonomous systems and dynamic route optimization become commonplace. The analysis demonstrates how AI can be a critical factor in moving naval operations into a new era of efficiency and proactive threat management. However, responsible development and ethical considerations remain of paramount importance.